2020
DOI: 10.3389/fcimb.2020.567268
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Changes in Patients With Postpartum Depressive Disorder

Abstract: Postpartum depressive disorder (PPD) is a unique subtype of major depressive disorder and a substantial contributor to maternal morbidity and mortality. However, the pathogenesis of PPD has still remained elusive, and it may associate with genetic and environmental factors. Gut microbiota has already been proved to be associated with depression; however, a limited number of studies have concentrated on PPD. The present study aimed to explore the potential correlations between gut microbiota and PPD. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 63 publications
3
39
1
Order By: Relevance
“…Chinese medicine is ineffective in sterile animals, which suggests that its function relies on interactions with microflora ( Kato et al., 2007 ). In a previous work on postpartum depression by our group, we found that postpartum depression is associated with intestinal microflora disorders in both humans ( Zhou et al., 2020 ) and rats ( Ramsteijn et al., 2020 ).…”
Section: Introductionmentioning
confidence: 78%
“…Chinese medicine is ineffective in sterile animals, which suggests that its function relies on interactions with microflora ( Kato et al., 2007 ). In a previous work on postpartum depression by our group, we found that postpartum depression is associated with intestinal microflora disorders in both humans ( Zhou et al., 2020 ) and rats ( Ramsteijn et al., 2020 ).…”
Section: Introductionmentioning
confidence: 78%
“…In this study, these differential OTUs mainly belonged to families under Firmicutes (Lachnospiraceae, 8 OTUs; Oscillospiraceae, 6 OTUs; Ruminococcaceae, 6 OTUs) and families under Bacteroidota (Bacteroidaceae, 4 OTUs; and Rikenellaceae, 3 OTUs). Previous studies have found that the abundances of Lachnospiraceae, Ruminococcaceae and Bacteroidaceae were changed in both depressed mice and patients ( Park et al., 2020 ; Zhou et al., 2020 ; Liu X. et al., 2021 ). Park et al.…”
Section: Discussionmentioning
confidence: 96%
“…In our previous work, we found significant differences in gut microbiota compositions between MDD patients and healthy controls (HC) ( Chen et al., 2020 ; Bai et al., 2021 ), and these differences were specifically relative to bipolar disorder and schizophrenia ( Zheng et al., 2019 ; Zheng et al., 2020 ). Other researchers also found that some bacterial taxa, such as Flavonifractor and Faecalibacterium , changed in patients with depression ( Coello et al., 2019 ; Zhou et al., 2020 ; Coello et al., 2021 ). Using an animal depression model, we reported that gut microbiota could induce depression-like behaviors by regulating the host’s metabolism ( Zheng et al., 2016 ) and that glycerophospholipid metabolism might be the vital node between microbiota and depression ( Tian et al., 2022 ).…”
Section: Introductionmentioning
confidence: 91%